Diabetes Management Delivery and Pregnancy Outcomes in Women with Gestational Diabetes Mellitus during the First Wave of the 2020 COVID-19 Pandemic: A Single-Reference Center Report - Magdalena Wilk; Paulina Surowiec; Bartłomiej Matejko; Albert Wróbel; Joanna Zięba-Parkitny; Katarzyna Cyganek; Hubert Huras; Maciej T. Małecki (Journal of Diabetes Research)
Objectives. The COVID-19 pandemic has forced a rapid adaptation of healthcare services to secure care for many patient groups. This includes women with gestational diabetes mellitus (GDM). We evaluated the impacts of the first COVID-19 wave on parameters such as the GDM treatment, glycemic control, and pregnancy outcomes. Methods. In this retrospective study from a reference diabetes center (Krakow, Poland), we compared patient data from two different time periods: the first wave of the COVID-19 pandemic (March 2020–June 2020) and the preceding five months (October 2019–February 2020). Data was collected from the medical records and telephone surveys. Results. We included 155 consecutive women (group N1=73 and group N2=82 from the COVID-19 pandemic period and non-COVID-19 period, respectively). During the COVID-19 pandemic, almost half of all GDM women (N1=36, 49.3%) used telemedicine as a method of contacting their diabetic specialists while this tool was not utilized in the earlier period. Moreover, these patients reported difficulties in performing blood glucose self-control more often (N1=20, 27.4%, vs N2=7, 8.5%; p≤0.01) and spent less time on diabetes education than the control group on average (N1=39, 53.4%, vs N2=9, 9.8% below 2 hours of training; p≤0.01). Most analyzed glycemic parameters and pregnancy outcomes were similar. Differences were found with respect to the incidence of prolonged labor (N1=12, 16.4%, vs N2=3, 3.7%; p≤0.01) and preeclampsia (N1=0 vs N2=7, 8.5%; p=0.01). Conclusion. In this single-center observational study, the first wave of the COVID-19 pandemic did not seem to have a negative impact on pregnancy outcomes in GDM women, despite the difficulties in diabetes management delivery.